ETHNOGRAPHISMS IN THE NOVEL “ELEN-ALAN” - Anes, G.; Soilemez, O.; Burkitbayeva, A. (A.Baitursynuly Institute of Linguistics, 2024)
In the modern era of developed globalization, the main driving force for the formation of a nation, integration as a people, unification as a country, preservation of national traditions is our ethnic mentality, language, religion and actual thinking. The main idea of the study is to cite ethnographic data from the historical novel “Elen-Alan”, which reflects the history, traditions and thoughts of our nation, using local color phraseology, proverbs and sayings in the language of the writer. The article aims to identify the content of individual phrases and phrases that determine the language skills of the writer by conducting an ethnolinguistic study of Ethnography in the language of A. Kekilbayev. The relevance of the study is manifested in the justification within the framework of linguistic ethnographisms that the ethnocultural unity of the writer's language forms a fund of ethnolexic words. The novelty and value of the topic of the article is emphasized by the fact that the study of phrasal phrases and parables related to domestic customs, traditions and customs that reflect the national character in the language of the writer is taken and evaluated in a holistic context. In the course of the study, methods of systematization and description of language material were used. The need to collect ethnographisms in the writer's language and create a systematic dictionary as future perspectives of the research was determined.